Analysis of Environmental Factors in Stunting Locus Areas - Muslimin, Irma; Salim, Andi; Fajriana, Hasmar (GLOBAL HEALTH SCIENCE GROUP, 2023)
Shortness is identified by comparing a child's height with the standard height of children in a normal population of the same age and sex. The results of the 2021 Indonesian Nutrition Status (SSGI) study showed that the stunting rate in West Sulawesi was 33.38%. (Ministry of Health of the Republic of Indonesia, 2021) and 2022 shows that the prevalence of stunting nationally is 21.6% with the prevalence of stunting in West Sulawesi Province 35%. This research was conducted with a quantitative approach. Data was collected using a structured questionnaire to look at environmental factors related to stunting through the chi square test The results of the crosstabulation analysis of stunting incidents with sanitation conditions in Tabolang village after being categorized, found that the p value = 0.687. These results indicate that there is no relationship between sanitation conditions and the incidence of stunting in Tabolang Village. There was no relationship between environmental conditions and the incidence of stunting in this study. However, in order to prevent stunting in society, programs related to improving the environment need to be given attention and carried out through collaboration between the government and the community.